Cardioprotection by Cocoa Polyphenols and ω-3 Fatty Acids: A Disease-Prevention Perspective on Aging-Associated Cardiovascular Risk - Davinelli, Sergio (J Med Food, 2018)
Cardiovascular disease (CVD) remains the leading cause of death today. Many of the biochemical alterations associated with the pathophysiology of CVD can be modified by adequate intakes of bioactive nutrients through a correct diet or supplementation. Recently, there has been growing public and clinical interest in cocoa polyphenols (CPs) and omega-3 (ω-3) fatty acids. A plethora of nutritional intervention trials and experimental studies demonstrates that consumption of these bioactive food compounds is beneficial to promote cardiovascular health. The purpose of this review is to summarize the major cardioprotective effects of CPs and ω-3 fatty acids, providing a scientific rationale for incorporating the combination of these molecules as a nutritional intervention in the prevention of CVD. Although several studies have shown the individual cardioprotective nature of these compounds, a combination treatment with CPs and ω-3 fatty acids may be a promising approach to enhance the preventive value of these molecules and reduce cardiovascular risk factors associated with aging. Therefore, this article also reviews some of the key studies on the interaction between CPs and the metabolism of ω-3 fatty acids.